Hubungan Tingkat Pendidikan Dengan Kejadian IUGR Di Rsud Prof. Dr. W. Z. Johannes Kupang Pada Tahun 2021 - Putera, Dewa Gede Agung Sasmara; Ngga, Yoseph Mariano Aprio; Mamo, Hendriette Irene (Cendana Medical Journal, 2023)
Intra Uterine Growth Restrictions (IUGR) are defined as fetal growth rates less than normal fetal growth potential for certain neonates or failure of the fetus to reach its growth potential. The greatest incidence of intrauterine growth restriction in developing countries is multifactorial and involves a complex collaboration of fetal, placental and maternal factors, although maternal factors are the predominant cause. The purpose of this study was to determine the relationship between education level and the incidence of IUGR at RSUD Prof. Dr. W.Z. Johannes Kupang. This research is a descriptive study using a retrospective cross-sectional method. Data collection was carried out in November 2022 - January 2023 at RSUD Prof. Dr. W. Z. Johannes Kupang, East Nusa Tenggara. Samples were taken by total sampling with the number 110 samples being the final smaples. The results of this study indicate that there is a relationship between education level and the incidence of IUGR. The value of each Pearson Correlation variable is 0.711 which means r count > from r table (0.245 with a significance value of 0.005). If the calculated r value is greater than the r table value, the Pearson Correlation analysis means that there is a correlation with these variables